The Discriminatory Nature of Specific Tariffs - Chowdhury, Sohini (Oxford University Press on behalf of the World Bank, 2013)
This paper quantifies the distortions from specific tariffs levied by the EU. The most-favored-nation (MFN) specific tariffs levied by the EU translate into higher tariff barriers for poor countries exporting low price goods. We show that for poor countries, these higher tariff barriers from specific tariffs offset the gains from preferential tariffs. We apply a two-stage analysis to show that the specific tariffs levied by the EU on its agricultural imports wash away more than half of the welfare benefits enjoyed by the Sub-Saharan African countries from EU preferential tariffs. Our results provide the first quantitative estimate of the distortions associated with specific tariffs.